ALAM DAN MANUSIA MENURUT MASYARAKAT DESA RUMENGKOR - Karundeng , Yustinus Realino; Lefteuw, Frienscio George; Mayabubun, Yohanes Berty (Department of Theology - Sekolah Tinggi Filsafat Seminari Pineleng, 2025)
Nature and humans are two entities that cannot be separated from each other. Both are in an integral unity that is interdependent. This pattern has been lived by local communities for a long time. Their lifestyle is more friendly to nature than the modern anthropocentric pattern. The Tombulu community in Rumengkor Village has a unique understanding and appreciation of the relationship between nature and humans. The pattern of appreciation clearly shows mutual respect and appreciation, the importance of nature conservation, and harmony. Humans are part of nature as an integral organic unit, which can coexist in a harmonious relationship. This paper aims to explore this through a qualitative-descriptive approach, with a descriptive-analytic writing style.